FLOW ANALYSIS AND MODELING OF THE LAKE ÁGUA PRETA: WATER SOURCE OF THE BELÉM METROPOLITAN AREA - Holanda, P. S.; Blanco, C. J. C.; Cruz, D. O. A.; Lopes, D. F.; Barp, A. R. B.; Secretan, Y. (Revista de Engenharia Térmica, 2010)
The natural conditions of water resources can be modified with the unsustainable use of them. For example, in Belém, capital of Pará State, Água Preta Lake has a history of degradation jeopardize the drinking water supply in Belém. Thus, the main contribution of this work is to develop a study on modeling hydrodynamic study of Água Preta Lake. Such study is carried through the bathymetric of 2009 performed with an ADCP. The bathymetry and substrate data that composes the Lake and its boundary. The bathymetry data are used to construct the digital elevation model, with the coordinates x, y and z in UTM; while the composition of the substrate is used for the determination of the Manning coefficient. The coordinates x, y, z and Manning coefficient are used in the hydrodynamic model. This one is the classic model of Saint-Venant. In this case, a vertical integration is applied to the three-dimensional equations of Navier-Stokes for incompressible flow with outline conditions, of bottom and of liquid and solid surface, included. Thus, the problem becomes two-dimensional (2D) and the values obtained for velocities are medium in the vertical direction. The velocities are the input data for the many models, such as pollutant dispersion sediment transport and aquatic fauna and flora habitats. Thus, besides of hydrodynamic model explains the patterns of flow in the lake, it can be employed for the others models of the Lake Água Preta.